Scoping Review: Strategies For Managing Non-Conformities In Implementing Construction Contracts In Timor-Leste. - João Quintão do Rêgo; Aryuanto Soetedjo; Nusa Sebayang; Nanta Sigit (Citakonsultindo, 2025)
The construction sector in Timor-Leste plays a vital role in supporting national development and economic growth, primarily through infrastructure projects financed by the government and international donors. However, the implementation of construction contracts in the country frequently encounters various nonconformities, such as delays, technical specification changes, differing interpretations of contract clauses, and cost overruns. These issues reflect weaknesses in contract management systems and the lack of systematic strategies to manage nonconformities during project execution. This study employs a Scoping Review approach to map globally reported strategies for managing construction contract nonconformities and to identify knowledge gaps in developing country contexts, particularly Timor-Leste. The review process follows the PRISMA-ScR guideline, encompassing literature searches in Scopus, ScienceDirect, Taylor & Francis, and Google Scholar databases covering publications from 2000 to 2025. The findings reveal that management strategies for contract nonconformities can be categorized into three main groups: preventive strategies (risk prevention through clear contract design and early communication), resolutive strategies (dispute handling via claims, mediation, and dispute boards), and adaptive strategies (contract flexibility and collaborative approaches). The study highlights the importance of adapting global best practices to the local context of Timor-Leste, taking into account institutional capacity, contractual regulations, and human resource competence. The findings are expected to serve as a foundation for developing more effective contract management policies and practices within Timor-Leste’s construction sector.